Women's experiences of induction of labour: Qualitative systematic review and thematic synthesis. (February 2019) - Coates, Rose; Cupples, Georgina; Scamell, Amanda; McCourt, Christine
Highlights: Ten interview studies of women's experiences of induction of labour were identified. Women did not feel involved in decision-making regarding induction of labour. Women were unprepared for many aspects of the induction process. Support from healthcare providers is vital for women undergoing induction. Three studies considered outpatient induction of labour. Abstract: Objectives: To explore and synthesise evidence of women's experiences of induction of labour (IoL). Design: Systematic review and thematic synthesis of peer-reviewed qualitative evidence. Relevant databases were searched from inception to the present day. Study quality was appraised using the Critical Appraisal Skills Programme (CASP) qualitative research appraisal tool. Setting and participants: Low and high risk women who had experienced IoL in an inpatient or outpatient setting. Findings: Eleven papers (representing 10 original studies) published between 2010 and 2018 were included for thematic synthesis. Four key analytical themes were identified: ways in which decisions regarding induction were made; women's ownership of the process; women's social needs when undergoing IoL; and the importance of place in the induction process. The review indicates that IoL is a challenging experience for women, which can be understood in terms of the gap between women's needs and the reality of their experience concerning information and decision-making, support, and environment. Key conclusions and implications for practice: Providing good quality appropriately timed information and supporting women's self-efficacy to be involved in decision-making around IoL may benefit women by facilitating a sense of ownership or control of labour. Compassionate support from significant others and healthcare professionals in a comfortable, private and safe environment should be available to all women.